A textile-based triboelectric nanogenerator for long jump monitoring. (15th October 2022) - Liu, Ru; Li, Mingping
ABSTRACT: Triboelectricnanogenerators (TENGs) is an efficient mechanical-electrical energy conversion method based on contact electrification and electrostatic induction coupling effect. The research on the application of TENGs is very necessary and valuable. Long jump is an influential and rapidly developing sport in sports. In this work, we designed a novel cotton cloth-based triboelectric nanogenerator (CC-TENG) to both harvest mechanical energy and monitor long jump. The cotton cloth and polydimethylsiloxane (PDMS) is used as the triboelectric layer. The prepared CC-TENG device has the advantages of portability, flexibility and foldability. The CC-TENG can achieve the maximum output power of 1.53 mW at a load of 9 MΩ. Moreover, the excellent reliability of CC-TENG can be observed. The CC-TENG was designed as the array CC-TENG to monitor long jump. This design will help to improve athletes' training results and promote the development of intelligent sports.